The role of epigenetic changes in preeclampsia. (25th July 2019) - Kamrani, Amin; Alipourfard, Iraj; Ahmadi‐Khiavi, Homayoon; Yousefi, Mehdi; Rostamzadeh, Davood; Izadi, Morteza; Ahmadi, Majid
Abstract: Preeclampsia (PE) is a disorder affecting 2–10% of pregnancies and has a major role for perinatal and maternal mortality and morbidity. PE can be occurred by initiation of new hypertension combined with proteinuria after 20 weeks gestation, as well as various reasons such as inflammatory cytokines, poor trophoblast invasion can be related with PE disease. Environmental factors can cause epigenetic changes including DNA methylation, microRNAs (miRNAs), and histone modification that may be related to different diseases such as PE. Abnormal DNA methylation during placentation is the most important epigenetic factor correlated with PE. Moreover, changes in histone modification like acetylation and also the effect of overregulation or low regulation of miRNAs or long noncoding RNAs on variety signaling pathways can be resulted in PE. The aim of this review is to describe of studies about epigenetic changes in PE and its therapeutic strategies.